2010
DOI: 10.1016/j.neures.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms of schizophrenia correlate with impairment on the University of Pennsylvania Smell Identification Test

Abstract: Deficits in odor identification have been the most frequently described in schizophrenia (SZ). A relationship between dysfunction in odor identification and negative symptoms of SZ has also been reported. Furthermore, deficit SZ (a subtype of the illness with primary, enduring negative symptoms) has been found to be associated with a particularly poor performance on odor identification tests indicating that deficits in smell identification could be differentially expressed in some subtypes of SZ. We describe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 43 publications
(66 reference statements)
2
40
2
Order By: Relevance
“…Kayser et al, 2013;Turetsky et al, 2008), allow sensory information to reach orbitofrontal regions (Brewer et al, 2006). This hypothesis is supported by the findings that OI deficits are associated with negative symptoms (Brewer et al, 1996a(Brewer et al, , 2001Corcoran et al, 2005;Good et al, 2006;Ishizuka et al, 2010) and more specifically, the deficit syndrome of schizophrenia (Strauss et al, 2010).…”
Section: Introductionmentioning
confidence: 77%
“…Kayser et al, 2013;Turetsky et al, 2008), allow sensory information to reach orbitofrontal regions (Brewer et al, 2006). This hypothesis is supported by the findings that OI deficits are associated with negative symptoms (Brewer et al, 1996a(Brewer et al, , 2001Corcoran et al, 2005;Good et al, 2006;Ishizuka et al, 2010) and more specifically, the deficit syndrome of schizophrenia (Strauss et al, 2010).…”
Section: Introductionmentioning
confidence: 77%
“…Links between loss of smell, anhedonia and reduced quality of life have been recently described, 42,43 as has an asso ciation between anhedonia and decreased performance on smell identification. 21 Increased ability to identify the origins of odours may heighten vigilance and produce fear in individuals unable to use higherlevel processes to evaluate the context of the sen sory experience. The amygdala plays central roles in both odour perception and response to aversive stimuli and in the awareness and expression of fear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of college students demonstrated better SIT performance for those with elevated social anhedonia, 20 but another study conversely found lesser performance for individuals with anhedonia, blunted affect and apathy, 21 con sistent with the results in patients with schizophrenia. The as sociation between olfaction and anxiety is unstudied in pa tients with schizophrenia, but SIT deficits have been found in patients with obsessive-compulsive disorder (OCD) 22 and posttraumatic stress disorder (PTSD).…”
Section: J Psychiatry Neurosci 2015;40(6)mentioning
confidence: 90%
“…Given the magnitude of this deficit, it has been proposed that olfaction deficits also reflect a vulnerability marker for schizophrenia-spectrum disorders. Related to this, there is a strong background of existing literature that links negative symptoms of schizophrenia to olfaction accuracy (Ishizuka et al, 2010). Often, negative symptoms are specifically linked to the first episode of psychosis (Corcoran et al, 2005).…”
Section: Objective and Subjective Olfaction Across The Schizophrenia mentioning
confidence: 99%